Analisis Pengembangan Usaha Mikro, Kecil Dan Menengah (UMKM) Berbasis Ekonomi Kreatif Di Kabupaten Mamuju - Halim, Abdul (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
The objectives of this study are 1. To find out the growth of creative economy-based UMKM in Mamuju Regency, 2. To find out the development of creative economy-based UMKM in Mamuju Regency. This study uses types and data sourced from qualitative data and quantitative data. Legitimacy analysis is an analysis conducted to determine the credibility test. According to Sugiono (2012; 121) that "the credibility test is a way to find out the results of qualitative research by seeing or believing in the results obtained by looking at data collection methods through interviews or observing directly. The results of the analysis explain that the growth of UMKM in general in Mamuju Regency is good, this is evidenced that the growth that occurred from 2019 was 5.1, in 2020 it was 14.3 and in 2021 it was 9.4. The development of UMKM based on the creative economy is good, based on the results of interviews with informants representing the government, UMKM observers and creative economy business actors indicating that business development efforts are quite good, even though there was a decrease in turnover at the start of Covid 19 but it is now normal, even the turnover of business actors the creative economy is increasing in line with the existence of various trainings carried out by government agencies.